Political pragmatism and conceptual updating as a way of safeguarding a legacy: the transition of management of the Instituto Indigenista Interamericano and its magazine América Indígena from Manuel Gamio to Miguel León-Portilla (1960-1962): Pragmatismo político e atualização conceitual como forma de resguardar um legado: a transição da direção do Instituto Indigenista Interamericano e sua revista América Indígena de Manuel Gamio para Miguel León-Portilla (1960-1962) (Revista de História da UEG (REVHIST), 2024)
We present an excerpt from our ongoing research that uses as a source the official publication of the Instituto Indigenista Inteamericano, the magazine América Indígena. Its first issue was published in 1941 and from 1942 its editorial line was guided by the positions of the influential Mexican anthropologist Manuel Gamio. As we know, his proposal, broadly speaking, was to incorporate indigenous people into Western culture through cultural miscegenation. However, América Indígena magazine was also characterized as an open space for debate between different views and positions. However, the “indigenous incorporation” project was the one favored by the I.I.I. under the direction of Manuel Gamio (1942-1960). In this paper, we propose to address transformations and continuities in the transition of the editorial line of América Indígena magazine, from the last year of Manuel Gamio's direction (1960) to the first years of its new director: Miguel León-Portilla (1961-1962).Keywords: Indigenism. Magazine. Latin America.